Pengaruh citra merek dan promosi terhadap keputusan pembelian produk Uniqlo - Sitinjak, Tumpal Janji Raja; Arief, Ajeng Rossa Aulia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Technology and information in recent years are growing rapidly and communication tools that are much in demand by the public, namely through the internet. One of the visible developments of this technology is gadgets so that the tendency to engage in online activities such as chat, e-mail, browsing and online shopping is easier to access. Fashion and accessories occupy the number 1 product sought after when shopping online, so the author is interested in conducting brand image research and promotion of Uniqlo product purchase decisions through Uniqlo online store. The object of this research is a Uniqlo product purchased online through the Uniqlo website or application. Researchers collected questionnaire data using Google Form, a sample withdrawal by way of nonprobability sampling with the Judgement Sampling approach. The conclusion in this study is that brand image and promotion have a positive influence on purchasing decisions.